HUBUNGAN TINGKAT PENGETAHUAN LANSIA DENGAN TINGKAT KEMANDIRIAN ADL (ACTIVITY DAILY LIVING) PENANGANAN COMORBID COVID-19 DI PUSKESMAS KENJERAN SURABAYA. - Hisayatus Sya'diyah; Diyan Mutyah; Ayu Citra Mayasari; Sukma Ayu Candra Kirana; Ali Gufron (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2022)
Background: Covid-19 attacked all ages without exception, the corona virus was more dangerous if it attacked an elderly person who carries congenital diseases such as diabetes mellitus, chronic asthma sufferers, and hypertension. The lacked of good knowledge of the elderly in dealing with comorbidities such as hypertension can cause the elderly to be at high risk of contracting covid 19. Knowledge was needed so that the elderly are protected from exposure to the virus, the role in the family was also important to keep one of the families from contracting covid 19. Purpose: This study aims to determine the relationship the level of knowledge of the elderly with the level of independence of ADL (Activity Daily Living) in handling comorbid Covid-19 at the Kenjeran Health Center Surabaya. Methods: The design of this research was correlational analytic with cross sectional approach. The sample used Simple Random Sampling as many as 70 elderly people at the Kenjeran Health Center Surabaya. The independent variable in this study was the level of knowledge as measured by the knowledge questionnaire instrument according to Arikunto. The dependent variable in this study was the level of independence as measured by the Barthel's Index questionnaire instrument. Data analysis used Spearman rho test =0.05 Result: The results of this study indicated that the results of a study of 70 respondents have a relationship between the level of knowledge of the elderly and the level of independence in handling comorbid covid 19 at the Kenjeran Public Health Center Surabaya with = 0.032 (? = <0.05) Conclusion: The implication of this study was that the level of knowledge of the elderly played an important role in increasing the level of independence of the elderly in handled with comorbid covid-19, so that it requires early attention and treatment by nurses, families and other health workers Keywords: Elderly, knowledge, level of independence